2004
DOI: 10.1039/b408530b
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the lowest singlet and triplet excited states of S-flurbiprofen

Abstract: The photophysical properties of S-flurbiprofen [S-2-fluoro-alpha-methyl-4-biphenylacetic acid], a nonsteroidal anti-inflammatory drug, have been examined using steady-state and time-resolved spectroscopic techniques. The energy of its first singlet excited state is 99 kcal mol(-1). The fluorescence quantum yields and lifetimes (at 300 nm) have been determined in acetonitrile, methanol, hexane and PBS; they are in the range 0.15 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 27 publications
3
77
0
Order By: Relevance
“…Jimenez reported that irradiation of naproxen in the presence of β-CDs leads to more rapid disappearance of the drug naproxen. 24 It appears that photohaemolytic activity of diclofenac is reduced in the presence of β-CDs. This can be attributed to the different behavior of the complexed radical intermediates, rather than to greater drug photostability.…”
Section: Photodegradation Of Diclofenac With Cdsmentioning
confidence: 99%
“…Jimenez reported that irradiation of naproxen in the presence of β-CDs leads to more rapid disappearance of the drug naproxen. 24 It appears that photohaemolytic activity of diclofenac is reduced in the presence of β-CDs. This can be attributed to the different behavior of the complexed radical intermediates, rather than to greater drug photostability.…”
Section: Photodegradation Of Diclofenac With Cdsmentioning
confidence: 99%
“…From the photophysical point of view, FBP contains a biphenyl chromophore with well-known properties. 14 It exhibits a non-negligible intersystem crossing yield, so both the singlet and 55 triplet states can in principle serve to monitor its binding to a protein. Indeed, previous laser flash photolysis studies on FBP/HSA complexes showed that FBP binds to both sites I and II, but with higher affinity to site II.…”
Section: Introductionmentioning
confidence: 99%
“…2, 52.1, 114.9, 119.4, 127.0, 127.9, 129.0, 129.3, 130.8, 136.8, 141.8, 152.5, 174.7 1H, J = 8.0Hz), 6.28 (s,1H),6.50 (d,1H,J = 2.4 Hz),6.80 (m,2H),4H),10H),8.11 (bs,1H). 13 C-NMR (CDCl3) (, ppm) 18. 3, 27.5, 46.8, 52.6, 52.8, 109.5, 111.4, 115.1, 118.6, 119.7, 120.2, 122.2, 123.2, 127.5, 127.9, 129.0, 5 129.2, 130.9, 136.1, 137.5, 142.2, 153.3, 172.5, 173.9 N-[2-(S)-(2-Hydroxy-1,1'-biphenyl-4-yl) 4, 46.7, 52.4, 52.9, 109.9, 111.2, 115.1, 118.6, 119.7, 120.0, 15 122.2, 122.3, 127.2, 127.6, 127.7, 129.1, 130.7, 136.0, 137.1, 141.7, 152.9, 172.3, 173.3 …”
Section: Characterisation Of the New Compoundsmentioning
confidence: 99%